2004
DOI: 10.1136/jnnp.2004.036574
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in neprilysin gene affect the risk of Alzheimer's disease in Finnish patients

Abstract: Objectives: Neprilysin (NEP) is an amyloid b-peptide (Ab) degrading enzyme expressed in the brain, and accumulation of Ab is the neuropathological hallmark in Alzheimer's disease (AD). In this study we investigated whether polymorphisms in the NEP gene have an effect on the risk for AD. Methods: The frequencies of seven single nucleotide polymorphisms (SNPs) and apolipoprotein E (APOE) were assessed in 390 AD patients and 468 cognitively healthy controls. Genotypes of the study groups were compared using binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…11 Population genetic studies suggest that polymorphisms in the neprilysin gene are associated with altered risk of lateonset AD. 16,17 Together, these studies suggest that neprilysin plays a vital physiological role in Ab clearance and support the hypothesis that elevating neprilysin activity in brains containing high Ab levels is likely to lower Ab levels and may ameliorate AD pathology and symptoms.…”
Section: Introductionsupporting
confidence: 63%
“…11 Population genetic studies suggest that polymorphisms in the neprilysin gene are associated with altered risk of lateonset AD. 16,17 Together, these studies suggest that neprilysin plays a vital physiological role in Ab clearance and support the hypothesis that elevating neprilysin activity in brains containing high Ab levels is likely to lower Ab levels and may ameliorate AD pathology and symptoms.…”
Section: Introductionsupporting
confidence: 63%
“…Here, we identified not only APP but also its regulators such as membrane metalloendopeptidase (Mme) and protein phosphatase 3, catalytic subunit, ␣ isoform (Ppp3ca). Mme has a role in the degradation of excess and misfolded APP peptide (64), and the activity of protein phosphatase tightly regulates APP secretion (65). In addition, we found six proteins that are related to diabetes, a disease characterized by insulin resistance and hyperinsulinemia.…”
Section: Distribution Of Glyco-and Phosphopeptides In Erlic-mentioning
confidence: 86%
“…In contrast, Thomas et al showed that the learning abilities were not reduced in older NEP knockout mice; rather, they were significantly improved, and Aβ deposits could not be detected by immunohistochemical methods, in spite of the elevated Aβ levels in the brains of these mice 46. In humans, no mutation in the MME gene linked to familial Alzheimer's disease has been reported, although some nucleotide repeat polymorphisms have been reported to be associated with susceptibility to sporadic Alzheimer's disease 47, 48. We hypothesized that human NEP deficiency would lead to cognitive impairment and increased Aβ plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%